Analisis cara kerja bahasa pada konsep facelift Avanza-Xenia melalui pendekatan struktur visual - Wildan Aulia (Institut Seni Indonesia Yogyakarta, 2022)
In the context of design diversification, exploring forms to optimize product operations is no longer sufficient. One of the goals of design diversification is to emphasize meaning that goes beyond just the function of a product. This provides an understanding of how the product communicates with users. Design development aims at how design can communicate and persuade. Therefore, communication is related to the language system. This paper aims to analyze how the language system works which applies equally to product design. In this context, the product acts as text. The product sample selected in this study is the second-generation Avanza-Xenia car based on the consideration that the car is one of the cars that has a facelift concept with many variants. The study uses a visual structure approach. The analysis is carried out by extracting the structural elements of the car into the main elements and supporting elements, then matching them to the text structure. The results of the study show that providing multiple design variants on supporting elements of the car is the same as using alternative words to emphasize meaning